The Curriculum for Developing the “Creating Dream Stories Through AI” is Based on Storyline Learning for Year 6 Rome Students Under the Jurisdiction of Phitsanulok Municipality - Yuangsoi, Pichayapha; Boonrod, Peeradech (Academic Journal of Local Development, 2024)
The 2022 PISA results found that nearly 80% of students worldwide have basic creativity. For Thai students, more than half of them struggle to score at a basic creativity level. This resulted in Thailand being ranked 54th out of 64 countries in terms of creativity. Therefore, Thai educational agencies need to look at the problem and work together to develop creativity in children and learners by using various teaching methods and innovations that will help develop creativity. From the above reasons and results, the researcher is interested in conducting research to develop creativity in Grade 6 students of Phitsanulok Municipality. The objectives for this research were 1) To develop and evaluate the quality of a training curriculum titled "Creating Dream Stories through AI" using the storyline learning activity model for Grade 6 students under Phitsanulok Municipality. 2) To implement and study the effects of using the developed training curriculum, specifically: 2.1) Comparing the students' creativity after the training with the criterion of 75%. 2.2) Studying the satisfaction of the trainees towards the training activities. The sample group consisted of 70 Grade 6 students in the academic year 1/2567, selected through simple random sampling by drawing lots, with schools as the sampling units. The research tools used were: the training curriculum, activity plans, a creativity assessment form, and 4) Aasatisfaction questionnaire. The data analysis employed percentage, mean , standard deviation (S.D.), and a t-test one sample method. The findings were as follows: 1. The training curriculum consists of four components including curriculum objectives, content, training activities, and evaluation. The quality of the training curriculum was rated at the highest level. 2. The result of implementation training curriculum found as follow: 2.1 Score creativity after learning is significantly higher than the 75% with the criterion at a significance level of .05 2.2 The students' overall satisfaction with the training activities was rated at a high level.